METHODS FOR CELLULAR AND MOLECULAR COMPOUND OF ATHEROSCLEROTIC PLAQUES ASSESSMENT: LITERARY REVIEW - Yu. V. Saranchina; O. Yu. Kilina; S. V. Dutova; N. G. Polshcha; N. V. Khanarin; T. S. Kulakova (Кардиоваскулярная терапия и профилактика)
Recently, high prevalence of atherosclerotic lesion of the vascular walls and further development of cardiovascular pathology attracts the specialists from different fields. The main attention is paid to the risk factors of atherosclerosis and its clinical complications with the aim of prevention and treatment methods development. New knowledge from fundamental research of atherosclerosis at cellular and molecular levels facilitates the development of novel methods for prevention and treatment of the pathology. The article points on the review of the main modern laboratory tests for atherosclerotic plaques assessment. The opportunities discussed for the study of cellular contents of the plaques, as functional evaluation of the cells in plaques.